Gestão de habilidades sociais para estudantes com deficiência intelectual no contexto da educação profissional e tecnológica - Lehnhart, Gabriela Brutti (2022)
The general objective of this research was to elaborate and implement a plan focused on students with intellectual disabilities in Professsional and Technological Education, in order to improve the social relationships of these students in virtual environments, as well as to evaluate the effects of implementing this plan on the academic formation of the subject. Four students with intellectual disabilities from Professional and Technological Education participated in the research, their families and undergraduate students from the Special Education course, who were identified as academic facilitators. The study took place in the municipality of Santa Maria, in the state of Rio Grande do Sul, in one of the teaching units of the Federal University of Santa Maria, which promotes and teaches basic education, initial and continuing education, high school technical professional education and technological professional education. For reasons of the pandemic moment, the survey was carried out entirely in a virtual way, using online resources, such as the Google Meet and Whatsapp platform. To obtain the data, the following instruments were used: Support Intensity Scale (SIS) and the registration in the field diary. A quantitative analysis was carried out for both instruments, helping to build an intervention plan for students with disabilities. The observation protocol was also applied in the activities mediated by the academic facilitators and, finally, the social validity questionnaire with family members and guardians. Online meetings were held in 2020, through the Google Meet platform. The meetings took place weekly, with the students, the academic facilitators and the researcher, where we implemented the intervention plan with the student. In these meetings, we seek to clarify doubts regarding the current context and the guidelines on the changes occurred in the academic calendar. Discussions of the results were based on the analysis of the instruments applied. It is possible to identify the performance of the protagonists as satisfactory at all stages of the research, as well as highlighting new learning possibilities for students with intellectual disabilities in the virtual environment.